Effects of pesticides on soil microbial community structure and nitrogen transformation in tobacco fields affected by root rot - Li, Fengyu; Qiu, Zhaoguo; Pei, Zhouyang; Zhu, Qifa; Shen, Sideng; Fan, Linlin; Xu, Lvqin; Huang, Changquan; Wang, Jie; Huang, Bin; Huang, Leye; Liu, Xinyu; et al. (Frontiers in Microbiology, 2026)
IntroductionIn tobacco planting soil infected with root rot disease, the potential impacts of prothioconazole (T1), pyrisoxazole (T2), kasugamycin combined with Paenibacillus polymyxa (T3), and cyclobutrifluram (T4) on soil microecology remain unclear. This study examined their effects on soil microbial communities and nitrogen transformation processes.MethodsBy measuring soil nitrogen forms and enzyme activities, combined with metagenomic sequencing, we conducted a comprehensive assessment of the soil microecology, focusing on shifts in microbial community composition, xenobiotic degradation potential, and nitrogen cycling processes.Results and discussionThe results revealed that pesticide application significantly changed the content of nitrogen forms and their transformation rate. T1 and T2 treatments significantly increased the accumulation of ammonium nitrogen (NH4+-N), while T2 and T4 markedly promoted the accumulation of nitrate nitrogen (NO3–-N). Microbial community analysis indicated that the T2 and T4 treatments significantly affected the microbial structure. Analysis of xenobiotic degradation pathways showed that multiple pathways were suppressed by the four pesticide treatments, with the T2 treatment exhibiting the broadest suppressive effect. Metagenomic analysis further revealed that the T2 treatment promoted the accumulation of both NH4+-N and NO3–-N by up-regulating the mineralization gene (gdh) and nitrification genes (hao and nxrAB), while the T4 treatment facilitated NO3–-N accumulation by up-regulating nitrification genes (hao and nxrAB). Correlation network analysis uncovered relationships between key nitrogen cycle genes and microbial genera, showing that nitrification genes (hao and nxrAB) in the T2 and T4 treatment groups exhibited positive correlations with Nitrobacter and Nitrosovibrio. This research clarifies the pathways through which these four pesticides influence the soil nitrogen cycle, providing an important theoretical basis for their ecological risk assessment and rational application.